Acciones de enfermería y su relación con la prevención de la tuberculosis en adultos jóvenes atendidos en el subcentro Puerta Negra, junio – octubre 2023 - Madrid Naranjo, Paola Vanessa (2023)
Tuberculosis is currently a section that is derived from Mycobacterium tuberculosis, which mainly occurs in the lungs, you are the case that globally continues to make one of the deadliest pathologies with approximately 1,000,000 new cases according to statistical data. What is also known in this case study is intended to analyze the influence of nursing actions in relation to the prevention of tuberculosis so that the optimal state of health of young adults treated at the Puertas Negra health center benefits. In addition, the research design was mixed since the research and systematic review was implemented according to the data in vital information from the various platforms with the aim of being able to support the theoretical bases and in turn the implementation of surveys which allowed directly identify the difficulties within the study sample and in turn determine what are the incidences that occur with respect to the prevention of tuberculosis in young adults. In conclusion, due to the high frequency and prevalence of tuberculosis in the Ecuadorian population, it is important to implement each and every one of the biosafety measures to reduce the spread of these diseases. It is also important that there is a timely diagnosis and efficient treatment. current TB-positive patients to prevent the spread of the disease.